Ogimah Ikwe: Native Women and Their Path to Leadership - Lajimodiere, Denise K. (Wicazo Sa Review, 2011)
Much documentation gathered on Native American women's activities originated in the journals of European male missionaries and explorers. These first visitors observed Native societies through the eyes of their own culture, a culture in which male activities were the only happenings of note. 1 This bias led to indirect and distorted descriptions of Native American women's activities and beliefs. 2 Scholars who study Native American women today have made significant inroads into their histories; however, many interpretations remain incorrect and undeveloped. Devon Mihesuah states, "Because many authors write from a patriarchal or white feminist perspective, the value of Indian women is vastly underrated." 3 Gretchen Bataille and Kathleen Sands address this shortcoming, saying, "The portrayal of American Indian women in North America over the last four centuries offers an uneven body of documentary evidence about the lives of Native women as individuals and members of their group." This study's purpose is to increase the visibility of Native American women in leadership roles by recording the voices and histories of nine Native American women leaders. It focuses on the experiences, perceptions, and beliefs of the women interviewed, giving a voice to nine of today's Native American female leaders, nine Ogimah Ikwe (leader women).
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; cours; discipline; discours dominant; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; histoire et politique; patriarcat; pol4105; premier cycle; premières nations; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; travail; états-unis

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques